STAREGI KEPEMIMPINAN KEPALA MADRASAH SEBAGAI AGENT OF CHANGE DALAM MEWUJUDKAN MODERASI BERAGAMA - Lalu Sirajul Hadi (SOCIETY, 2021)
Madrasa is not only a place to study, but also a place to meet many people with different backgrounds, ideas, thoughts and ideas, which are different each other. Education in madrasa aims to make humans as creatures who believe and devote to Allah Almighty, by good religion, promoting goodness through the implementation of the teaching of Islam rahmatan lil’alamin (a blessing for all nature). One of the approaches taken to realize the religion of rahmatan lil’alamin is to recpect each other and tolerance for the achievment of harmonious and civilized human life goals. Moderate religious in madrasa is one method that can be place of religious education, which is not only about religious knowledge but also implemented in religious life in democratic life, through habituation and good attitude. The character of moderate religious requires openness, acceptance and coorporation from each of the diffrent groups and respect to others. Head master has a role in encouraging and moving these ideas and agent of change and reformer towards the good of the future for the young generation.